Correlation between social support, self-efficacy and quality of life in primary trigeminal neuralgia patients (原发性三叉神经痛患者社会支持、自我效能感与生活质量的相关性研究) - SUN Xiuxiu (孙秀秀); JIA Jianhua (贾建华); LI Yeyuan (李业园) (中西医结合护理)
Objective To explore the correlation between social support, self-efficacy and quality of life of patients with primary trigeminal neuralgia, and to provide reference basis for optimizing the quality of life. Methods Totally 220 primary trigeminal neuralgia patients who were 18 years old or older were conveniently selected from a tertiary hospital in Jinan City, and were surveyed with self-designed general information questionnaires, social support scales, chronic pain self-efficacy scales, and trigeminal neuralgia patients' quality of life questionnaires. Results The scores of trigeminal neuralgia patients were: social support (37. 82±8. 31), self-efficacy (61. 27±13. 17), and quality of life (81. 15±14. 75). There was a correlation between patients' quality of life, self-efficacy, and social support (P＜0. 05). Structural equation modeling showed that social support and self-efficacy were negatively correlated with quality of life, and self-efficacy had a significant mediating effect between social support and quality of life. Conclusion In clinical practice, healthcare professionals should enhance patients' quality of life by strengthening social support and improving patients' self-efficacy. (目的 探讨原发性三叉神经痛患者社会支持、自我效能感与生活质量的相关性, 为优化生活质量提供参考依据。方法 便利抽取济南市某三甲医院≥18岁的原发性三叉神经痛患者220例, 应用自行设计的一般资料调查问卷、社会支持评定量表、慢性疼痛自我效能量表以及三叉神经痛患者生活质量调查量表进行问卷调查。结果 三叉神经痛患者社会支持得分为(37. 82±8. 31)分, 自我效能感得分为(61. 27±13. 17)分, 生活质量得分为(81. 15±14. 75 )分。患者生活质量、自我效能感、社会支持之间均有相关性(P＜0. 05)。结构方程模型显示, 社会支持及自我效能感均与生活质量呈负相关, 自我效能感在社会支持和生活质量之间存在显著中介效应。结论 在临床工作中, 医护人员应通过加强社会支持、提升患者自我效能感, 进而提升患者生活质量。)